Cellulose-based substrate coated with barrier layer, laminated packaging material comprising cellulose-based substrate, and packaging container
By applying a base coating, a metallized coating and a thermally stable gas barrier top coating on the cellulose-based substrate to form a cellulose-based substrate, a cellulose-based substrate coated with a barrier layer is solved, and the non-aluminum foil laminated packaging material in the prior art is solved. The problem of insufficient gas barrier and heat sealability has achieved efficient oxygen barrier and heat sealability, and has good recyclability and sustainability.
Patent Information
- Application Number
- CN202380052067.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-18
- Filing Date
- 2023-07-14
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to provide a non-aluminum foil laminated packaging material with good gas barrier properties, heat sealability, recyclability and sustainability, especially in terms of packaging oxygen-sensitive products.
A cellulose-based substrate is used to form a laminated packaging material by applying a base coating and a metallization coating on the cellulose-based substrate and heating thereon a stable gas-barrier top coating. The material includes a cellulose-based substrate, a base coating, a metallized coating and a thermally stable gas barrier top coating.
It achieves good oxygen barrier properties and high-frequency induction heat sealing capabilities, while improving the recyclability and sustainability of materials. It is suitable for packaging of liquid, semi-liquid or viscous foods that are stored in long-term sterile.
Smart Images

Figure CN119487261A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a cellulose-based substrate coated with a barrier layer for packaging oxygen-sensitive products (e.g., foods). The present invention also relates to a method for manufacturing a cellulose-based substrate coated with a barrier layer, and a laminated packaging material comprising the cellulose-based substrate coated with a barrier layer, the packaging material being used for packaging oxygen-sensitive products (e.g., foods, such as liquid or semi-liquid foods), and to a packaging container comprising the laminated packaging material. Background Art
[0002] Disposable type packaging containers for single use of liquid foods are usually made of packaging laminates based on paperboard or cardboard. One such common packaging container is Tetra Brik The packaging containers are sold under the trademark of ANTI-FORMAT and are mainly used for aseptic packaging of liquid foodstuffs (e.g. milk, juice, etc.) that are sold for long-term ambient storage. The packaging material in such known packaging containers is usually a laminate material comprising a main body or core layer of paper, paperboard or other cellulose-based material and an outer liquid-tight layer of thermoplastic. In order to make the packaging container airtight, in particular oxygen-tight, for example for the purpose of aseptic packaging and packaging milk or juice, the laminate material in these packaging containers usually comprises at least one additional layer, most usually comprising an aluminum foil.
[0003] On the inside of the laminate, i.e. on the side intended to face the filled food content of the container produced from the laminate, there is an innermost layer applied to the aluminum foil, which innermost inner layer may consist of one or several partial layers, comprising a heat-sealable thermoplastic polymer, such as an adhesive polymer and / or a polyolefin. Likewise on the outside of the bulk layer, there is an outermost heat-sealable polymer layer.
[0004] Packaging containers are usually produced by modern high-speed packaging machines, which form packaging from packaging material coils or packaging material preforms, and fill and seal them. Therefore, packaging containers can be produced in the following manner: by welding the innermost and outermost heat-sealable thermoplastic polymer layers together, the two longitudinal edges of the coil are combined with each other at the overlap joint, and the laminated packaging material coil is transformed into a tube. The tube is filled with the expected liquid food, and then the tube is divided into each individual package by each repeated transversal seal of the tube, which is below the horizontal plane of the contents in the tube and at a predetermined distance from each other. The packaging is separated from the tube by the incision along the transversal seal, and the desired geometric configuration is obtained by folding and forming along the fold line prepared in the packaging material, and the desired geometric configuration is generally a parallelepiped. Before or after the container is filled, formed and sealed, each package can be equipped with an opening device, such as a screw plug.
[0005] The main advantage of this continuous tube forming, filling and sealing packaging process concept is that the web can be sterilized continuously before tube forming, thereby providing the possibility of an aseptic packaging process, i.e. a process in which the liquid contents to be filled as well as the packaging material itself are germ-reduced and the filled packaging containers are produced under clean conditions so that the filled packages can be stored for long periods of time even at ambient temperature without the risk of microbial growth in the filled product. As mentioned above, Tetra Another important advantage of the type packaging method is the possibility of continuous high-speed packaging, which has a considerable impact on cost efficiency.
[0006] Packaging containers for sensitive liquid foods (e.g. milk or juice) can also be made from sheet blanks or preformed blanks of the laminated packaging material of the present invention. The packaging is produced using a tubular blank of the packaging laminate folded into a plane by first erecting the blank to form an open tubular container capsule, one open end of which is closed by folding and heat-sealing integral end panels. The container capsule so closed is filled with the relevant food (e.g. juice) through its open end, which is then closed by further folding and heat-sealing the corresponding integral end panels. An example of a packaging container made from sheet and tubular blanks is the traditional so-called gable top package. There are also packages of this type with a molded top and / or a screw cap made of plastic.
[0007] The aluminum foil layer in the packaging laminate provides superior gas barrier properties to most other gas barrier materials. Traditional aluminum foil based packaging laminates for aseptic packaging of liquid foods also have inherent barrier properties to water vapor, light, aroma, taste and acidic substances and remain the most cost effective packaging material currently available in the market at its performance level. In addition, aluminum foil can be heat sealed and heated by induction in the aluminum foil.
[0008] Any other material comparable to aluminum foil-based materials must be cost-effective in terms of raw materials, have comparable food preservation properties, and have comparable low complexity in converting the material into a finished packaging laminate.
[0009] In the efforts to develop non-aluminum foil materials for liquid food carton packaging, there is also a motivation to develop prefabricated films or sheets with high barrier functions and multiple barrier functions, which can replace the aluminum foil barrier material in traditional laminated packaging materials, or be combined with other barrier layers in the laminated materials, and adapt them to conventional lamination and manufacturing processes.
[0010] A preferred type of such an alternative, more environmentally sustainable barrier material is a barrier coated paper substrate made by aqueous dispersion coating or vapor deposition coating on a thin paper carrier substrate. Various aqueous dispersion coating processes and vapor deposition coating processes and material formulations for achieving such coatings exist, but there is a need for a cost effective "non-foil" type (i.e. non-aluminum foil) barrier material having improved properties in terms of barrier properties, particularly against gases such as oxygen, for use in packaging laminates for liquid food packaging.
[0011] An earlier patent publication WO2011 / 003565A1 discloses a non-aluminium foil packaging material comprising a pre-coated and metallized kraft paper substrate for induction heat sealing purposes. It recommends a fairly thick coating and the inclusion of additional nanoclay particles in the pre-coating, and in order to obtain good gas barrier properties, a further barrier coating should also be applied in the packaging laminate, for example on the back side of the paper substrate or on the main paperboard layer.
[0012] Earlier patent publication WO2017 / 089508A1 discloses how to obtain further improved barrier properties from metallized paper in similar packaging laminates by selecting a paper substrate that provides the best performance. This metallized paper substrate not only provides improved barrier properties, but also shows that the metallized layer has better stability in induction heat sealing.
[0013] However, there remains a need for a more robust and reliable barrier-coated cellulose-based substrate that provides optimal oxygen barrier properties and reliable heat sealability via high frequency induction heating.
[0014] Often, there is also a need to improve the recyclability and sustainability of the materials used in order to reduce the amount of materials used and the number of different types of materials. Summary of the invention
[0015] Therefore, the object of the present invention is to provide a cellulose-based substrate coated with a barrier layer, which is suitable for use as a gas barrier material in the packaging of oxygen-sensitive products (such as foods, especially liquid or semi-liquid or wet foods), and for future sustainable non-aluminum foil-based ("non-foil") laminated packaging materials, which are used for heat-sealable packaging of oxygen-sensitive products by high-frequency induction heat sealing.
[0016] Another object of the present invention is to provide a cellulose-based substrate coated with a barrier layer having good gas barrier properties and high frequency induction heat sealing properties as well as improved recyclability and sustainability characteristics, i.e. meeting future demands for sustainable packaging materials for packaging oxygen sensitive products.
[0017] A more specific object is to provide a barrier coated paper or cellulose based substrate suitable for non-foil, heat sealable laminated packaging materials and packaging containers for liquid, semi-liquid or viscous foods to enable long term sterile storage under ambient conditions.
[0018] Another object is to provide a reliable paper or paperboard based heat sealable non-foil laminated packaging material having good gas barrier properties and having water vapour barrier properties, which is easily recyclable and environmentally sustainable for wrapping or packaging oxygen sensitive products such as food.
[0019] Another specific object of the present invention is to provide a non-foil, paper or paperboard based packaging laminate having reliable gas and water vapor barrier properties for use in making aseptic packaging containers for long term storage of liquid, semi-liquid or viscous foods under ambient conditions and while maintaining nutritional quality.
[0020] Thus, according to the present invention, these objects are achieved by a paper or cellulose based substrate, a laminated packaging material and a packaging container coated with a barrier layer as defined in the appended claims. SUMMARY OF THE INVENTION
[0021] According to a first aspect of the present invention, there is provided a cellulose-based substrate coated with a barrier layer, which is used as a barrier sheet in a heat-sealable laminated packaging material for packaging oxygen-sensitive products, the cellulose-based substrate coated with a barrier layer comprising: a cellulose-based substrate, and a base coating comprising more than 60% by weight of a material selected from the group consisting of starch, modified starch materials and cellulose ethers, the base coating being applied to the surface of a first side of the cellulose-based substrate by dispersion or solution coating and subsequent drying to provide a smooth and thermomechanically resistant base coating, and a metallized coating further applied to the free surface of the base coating, the metallized coating being applied by a vapor deposition method applied to the base coating, wherein the barrier-coated cellulose-based substrate further comprises a heat-stable gas barrier top coating, the heat-stable gas barrier top coating being applied to the metallized coating by dispersion or solution coating and subsequent drying, and wherein the heat-stable gas barrier top coating is also coated with or laminated to a heat-sealable thermoplastic material layer, the heat-stable gas barrier top coating having a higher melting temperature than the heat-sealable thermoplastic material layer, whereby the barrier-coated cellulose-based substrate has good gas barrier properties and is capable of achieving robust induction heat sealing conditions in a laminated packaging material to manufacture packaging from the laminated packaging material.
[0022] The base coating may comprise more than 70 wt%, such as more than 80 wt%, such as more than 90 wt%, such as more than 95 wt% of a material selected from the group consisting of starch, modified starch materials and cellulose ethers.
[0023] Preferably, the base coating comprises starch or a modified starch material.
[0024] The base coating may alternatively or also comprise a cellulose ether material. The base coating may replace or in addition to starch or starch-based materials, may also comprise one or more cellulose ethers selected from the group consisting of methylcellulose, ethylcellulose, carboxymethylcellulose (carboxymethyl cellulose) CMC, hydroxyethylcellulose HEC, hydroxypropylcellulose HPC, hydroxypropylmethylcellulose HPMC and sodium carboxymethylcellulose NaCMC.
[0025] Metallized coatings are vapor-deposited metal coatings, such as aluminum coatings.
[0026] The thermally stable gas barrier top coating may comprise a polymer selected from the group consisting of vinyl alcohol polymers and copolymers and modified such (co)polymers, for example selected from the group consisting of polyvinyl alcohol, PVOH, ethylene vinyl alcohol, EVOH and polymer mixtures comprising a majority (i.e., a proportion exceeding 50% by weight) of such polymers.
[0027] The substrate may be paper having a grammage of 30 g / m2 measured according to ISO 536:2012. 2 Up to 70g / m 2 , density measured according to ISO 534:2011 is 800kg / m 3 Up to 1400kg / m 3 .
[0028] According to a second aspect of the present invention, there is provided a method for manufacturing a cellulose-based substrate coated with a barrier layer for packaging oxygen-sensitive products, the method comprising the following steps:
[0029] a) conveying a continuous web of cellulose-based substrate;
[0030] b) providing an aqueous base coating composition comprising greater than 60 wt% on a dry weight basis of a material selected from the group consisting of starch, modified starch materials and cellulose ethers;
[0031] c) applying the aqueous base coating composition to the top surface of the cellulose-based substrate web by dispersion coating, such as roller coating;
[0032] d) drying the applied aqueous gas barrier polymer coating from step c) to provide a smooth base coating;
[0033] e) optionally repeating steps c) and d);
[0034] f) vapor deposition coating the dried web substrate coated with the base layer obtained in step e) with a metallizing coating;
[0035] g) applying an aqueous solution or dispersion of a thermally stable gas barrier top coating material to the metallized coating, preferably by roller coating,
[0036] h) drying the applied aqueous solution or dispersion from step g) to obtain a thermally stable gas barrier top coating,
[0037] i) optionally repeating steps g) and h),
[0038] j) thus obtaining a barrier-coated cellulose-based substrate having minimal defects in said base coating, said gas barrier top coating and said metallized coating,
[0039] k) further coating the surface of the heat-stable gas barrier top coating layer with a heat-sealable thermoplastic material layer, the heat-stable gas barrier top coating layer having a higher melting temperature than the heat-sealable thermoplastic material layer.
[0040] The thermally stable gas barrier top coating material may include a polymer selected from vinyl alcohol polymers and copolymers, such as the polymer selected from the group consisting of polyvinyl alcohol, PVOH, ethylene vinyl alcohol, EVOH, modified vinyl alcohol polymers and copolymers, and mixtures consisting essentially of such polymers, such as modified PVOH and modified EVOH.
[0041] According to a third aspect of the present invention, there is provided a laminated packaging material comprising a barrier-coated cellulose-based substrate produced by the method of the first aspect, and further comprising a first outermost protective material layer and a second innermost liquid-tight heat-sealable material layer.
[0042] The first outermost protective material layer may be a thin polymer layer, the purpose of which is to protect the paper-based or paperboard-based laminated packaging material from dirt and moisture in the environment outside the closed packaging container.
[0043] The second innermost layer of liquid-tight heat-sealable material may comprise a thermoplastic polymer layer which can be easily heat-sealed by available heat-sealing methods such as induction heat sealing or ultrasonic heat sealing, or simply contact heat sealing.
[0044] The second innermost layer of liquid-tight heat-sealable material may comprise a polyolefin polymer, such as a lower density range polyethylene, for example selected from the group consisting of LDPE, LLDPE, m-LLDPE and any mixture of two or more thereof.
[0045] According to one embodiment, both the first outermost protective material layer and the second innermost liquid-tight heat-sealable material layer may comprise a polyolefin polymer, such as the same or different types of polyethylene polymers.
[0046] For carton packaging of oxygen-sensitive products, such as liquid or semi-liquid or viscous foods, the laminated packaging material may also include a main body layer of paper or paperboard or other cellulose-based materials, and the cellulose-based substrate coated with the barrier layer is arranged on the inner side of the paper or paperboard main body layer, between the main body layer and the second innermost liquid-tight heat-sealable material layer. The main body layer can contribute to the bending stiffness of the laminated packaging material and to the dimensional stability of the folding and forming packaging container made therefrom to withstand the strong forces generated by the movement of the package contents (such as liquids and viscous oxygen-sensitive products) during distribution and handling. In such a laminated material, the metallized coating is preferably oriented toward the interior of the packaging container, that is, so that the cellulose-based substrate is oriented toward the main body layer and the barrier coating is oriented toward the innermost layer.
[0047] In one embodiment, to achieve such a liquid carton package, the second innermost liquid-tight heat-sealable polyolefin layer is a preformed polyolefin film, such as a preformed polyethylene film, such as an oriented polyethylene film, which includes at least one layer having a majority of LLDPE polymer to improve the robustness of the mechanical properties of the laminated packaging material.
[0048] A fourth aspect of the invention provides a packaging container comprising the laminated packaging material of the third aspect. According to one embodiment, the packaging container is at least partially made of the laminated packaging material of the invention, and according to another embodiment, it is entirely made of the laminated packaging material.
[0049] Therefore, the use of the cellulose-based substrate coated with a barrier layer of the present invention as described above can provide good gas barrier properties for laminated packaging materials and packaging containers made therefrom, and due to the increased content of cellulose fibers that are easily repulpable, can also impart improved repulpability and recycling properties, that is, improved sustainability.
[0050] In general, the use of cellulose-based substrates in laminates and packaging provides a greater proportion of fiber content that is both renewable, i.e., non-fossil-derived, and recyclable or biodegradable, thereby recycling old materials into the creation of new materials. In addition, the use of paper or cellulose-based substrates as "face layers" in sandwich structures supports the use of a body material with lower bending stiffness (and therefore less complex in designing for maximized bending stiffness) and / or lower density and therefore using a smaller amount of fiber (and therefore lower cost) by laminating such face layers on each side of the body layer.
[0051] Therefore, the cellulose-based substrate coated with a gas barrier layer according to the first aspect, and the resulting material layer structure, provide the laminated packaging material containing it with good oxygen barrier properties and good heat sealability, and can further impart good recyclability and sustainability characteristics. Detailed Description
[0052] The term "long-term storage" used in conjunction with the present invention means that the packaging container should be able to maintain the quality (i.e. nutritional value, hygienic safety and taste) of the packaged food under ambient conditions for at least 1 or 2 months, for example at least 3 months, preferably longer, for example 6 months, for example 12 months, or longer.
[0053] The term "package integrity" generally refers to the seal of the package, that is, the resistance of the packaging container to leakage or damage. The term includes the resistance of the package to the intrusion of microorganisms (such as bacteria, dirt and other materials) that may spoil the filled food and shorten the expected shelf life of the package.
[0054] One major contribution of a laminated packaging material to the integrity of a package is provided by good internal adhesion between adjacent layers of the laminate. Another contribution comes from the material's resistance to defects (e.g. pinholes, ruptures etc. within each material layer itself), and yet another contribution comes from the strength of the sealing joints by which the materials are sealed together when forming the packaging container. Therefore, for the laminated packaging material itself, the integrity characteristics usually focus on the ability to withstand thermal and mechanical loads (e.g. during folding and sealing) without breaking. More specifically, good adhesion between the individual laminate layers and their adjacent layers is required, as well as high quality of the individual material layers. With regard to the sealing of the package, the integrity focuses mainly on the quality of the sealing joints, which is ensured by good functional operation and robust sealing operation in the filling machine, which in turn is ensured by adequately adapted heat sealing properties of the laminated packaging material.
[0055] The term "liquid, semi-liquid or viscous food" generally refers to a food with a flowable content, which may optionally also contain solid food pieces. Dairy products and milk, soy, rice, grain and seed beverages, fruit juices, nectars, non-carbonated beverages, energy drinks, sports drinks, coffee or tea beverages, coconut water, wine, soups, crushed tomatoes, sauces (such as pasta sauce), beans and olive oil are some non-limiting examples of contemplated food products.
[0056] Examples of other oxygen sensitive food products that may be packaged and protected with the laminated packaging material of the present disclosure are, for example, dry and / or fatty foods.
[0057] The term "sterility" in relation to packaging materials and packaging containers refers to conditions under which microorganisms are eliminated, inactivated or killed. Examples of microorganisms are bacteria and spores. When a product is aseptically packaged in a packaging container, an aseptic process is usually used. In order to achieve continuous sterility during the shelf life of the package, the integrity of the package is of course very important. In addition, in order to achieve a long shelf life of the filled food, it may also be important that the package has barrier properties to gases and vapors (e.g. to oxygen) in order to keep its original taste and nutritional value intact, such as its vitamin C content.
[0058] The term "body layer" generally refers to the thickest layer or the layer containing the most material in a multilayer laminate, i.e., the layer that contributes most to the mechanical properties and dimensional stability of the laminate (e.g., thick paper, paperboard or cardboard) and the structural stability of a packaging container folded from the laminate. It may also refer to a layer that provides a greater thickness distance in a sandwich structure, which further interacts with a stabilizing surface layer having a higher Young's modulus on each side of the body layer to achieve sufficient such mechanical properties (e.g., bending stiffness) to achieve structural stability of a formed packaging container.
[0059] The term "non-foil" packaging material refers to laminated packaging materials that do not include aluminum foil with a thickness in the micrometer range, such as the conventional aluminum foil used for liquid carton packaging, which is usually 6μm to 9μm thick. However, "non-foil" packaging materials can include a metallized layer, such as an aluminum metallized layer with a thickness in the nanometer range. The amount of aluminum material used in such a metallized coating is very low, and the impact on the recycling and utilization of material resources is significantly reduced compared to aluminum foil.
[0060] The term "thermomechanical stability" with respect to a material or material layer refers to the ability of the material to maintain mechanical stability and geometry at elevated temperatures, even when the material is shaped or formed (e.g., pressed, folded, heat sealed), such that the metallization layer is well supported by such material or layer and does not degrade. In addition, the material does not melt or soften when heated to a predetermined temperature.
[0061] The OTR was measured using the Oxtran 2 / 21 (Mocon) instrument based on a coulometric sensor according to ASTM F1927-14 and ASTM F1307-14.
[0062] The method for determining OTR determines the amount of oxygen per surface and time unit that passes through a material at a specific temperature, at a given atmospheric pressure, over a specific time (i.e., over a 24-hour period in an atmosphere of 20% or alternatively 100% oxygen expressed at 0.2 or 1 atmosphere (oxygen)). See further description of the OTR test method associated with the Examples.
[0063] The sheet resistance (Rs) of the metallized coating can be measured by a non-contact method using a NAGY SRM-12 instrument from Nagy Instruments of Germany for laminated materials. The measurement setting range associated with the present invention is 0.2 to 8 ohms. The measurements are performed on laminated packaging materials and only on metallized materials, with a sample size of 0.05 m x 0.05 m (5 cm x 5 cm). Nine measurement points are taken from a 1 m long portion of a coil with a width of 0.17 m, i.e., three measurement points are located in the middle of the coil and three measurement points are close to each end of the coil portion. On a sample with uniform density, the sheet resistance is a value of R, and its main formula is R = density * L / W * t, where L and W are the sides of a square thin layer area, the area has the same length, and t is the thin layer thickness. The unit is ohm / square (Ω□).
[0064] Substrates suitable for the method of the invention are not limited to a certain type of paper or cellulose and also include other cellulose-based substrates, which are based on any type of fiber cellulose or fibril cellulose. However, the present invention is not suitable for substrates made of plastics or polymers, such as films made of regenerated cellulose, or films or papers made of or containing more than 50 wt% of so-called micro- or nanofiber cellulose (MFC or NFC), or papers with a layer or coating containing more than 50 wt% of MFC or NFC.
[0065] To be suitable for the final barrier coating step by a vapour deposition coating process, the cellulose based substrate needs to be thin and have a thickness of 30 to 70 g / m2 as measured according to ISO 536:2012. 2 , for example 30 to 60 g / m 2 , for example 35 to 50 g / m 2 , for example 35 to 45 g / m 2 and has a grammage of 800 kg / m 3 Up to 1400kg / m 3 , for example 900 to 1400 kg / m 3 , for example 950 to 1400 kg / m 3 For reasons of efficiency and production economy, and to avoid blistering of the coating due to air or moisture being trapped in the fibrous porous cellulose-based substrate during coating and drying operations, a cellulose-based substrate having a high density and a relatively low weight and thickness is desired. On the other hand, a grammage of less than 30 g / m 2 Cellulose-based substrates may be too mechanically weak and / or have poor dimensional stability when coated with a wet dispersion and subsequently dried, thereby exhibiting shrinkage or curling problems.
[0066] Therefore, it is more preferred to use a grammage of 30 to 50 g / m 2 , for example, most preferably 35 to 45 g / m 2 , density is 900kg / m 3 Up to 1400kg / m 3 Cellulose-based substrate.
[0067] The thickness of the cellulose based substrate may be 35 to 65 μm, such as 35 to 60 μm, such as 35 to 50 μm, such as 35 to 45 μm. It has been found that for certain applications, such as for liquid-tight packaging of wet or liquid or viscous products, it is also advantageous to use a high density paper substrate that is as thin as possible, as less polymer may be required in the adjacent liquid-tight or heat-sealable layer while maintaining the integrity of the packaging and its heat seal.
[0068] The roughness of the surface to be coated (top side or printing side) of the paper or cellulose based substrate suitable for the present invention may be less than 200 ml Bendtsen, for example 180 ml / min Bendtsen or less, for example 150 ml / min Bendtsen or less, for example 130 ml / min Bendtsen or less, for example 120 ml / min or less, for example 100 ml / min or less, for example 80 ml / min or less, for example 50 ml / min or less, for example 30 ml / min or less, for example 25 ml / min or less, measured according to ISO 8791:4.
[0069] If the surface roughness (measured as the Bendtsen value in ml / min) is too high, "valleys" and "peaks" will appear on the surface of the cellulose-based material, so that a thinly applied wet coating of an aqueous solution of a gas barrier polymer will not be able to fill and smooth the "valleys" nor cover the "peaks". In such a case, the applied and dried gas barrier polymer coating will not completely cover the surface, but will have defects through which oxygen molecules can easily penetrate through the coating. Therefore, the contribution of such a defective and insufficient barrier coating to the gas barrier properties will be significantly reduced. Rougher substrate surfaces naturally require the application of more polymer coating, which can be applied at lower coating line speeds. However, at high coating speeds, there are limits to how much aqueous coating can be applied, how much water can be evaporated in the drying operation, and how high the viscosity and solids content of the aqueous barrier polymer solution can be.
[0070] In embodiments, it is preferred that the surface roughness is less than 200 ml / min Bendtsen, such as less than 120 ml / min Bendtsen, such as less than 100 ml / min, such as less than 80 ml / min, such as less than 50 ml / min, such as less than 30 ml / min, such as less than 25 ml / min, so that the barrier coating performs better at industrially feasible high-speed operations. At less than 30 ml / min, the substrate surface is very smooth and a 0.5 g / m 2 A very thin coating of a thermally stable polymer or composition and still be able to completely cover and coat the surface.
[0071] Thus, the paper or cellulose based substrate coated with the base layer may have a lower roughness measured according to ISO 8791:4 than the substrate itself, for example 180 ml / min Bendtsen or less, for example 150 ml / min Bendtsen or less, for example 130 ml / min Bendtsen or less, for example 120 ml / min or less, for example 100 ml / min or less, for example 80 ml / min or less, for example 50 ml / min or less, for example 30 ml / min or less, for example 25 ml / min or less.
[0072] A good cellulose-based substrate may also have a coating surface of 30 g / m2 on the coated side ("top side" or "printing side") measured according to ISO 535:2014. 2 or lower in order to function well in coating processes for industrially manufacturing barrier-coated structures according to the present invention under feasible high speed conditions.
[0073] The Cobb 60 method according to ISO 535:2014 measures the water absorption of a cellulose-based substrate under standard conditions and is, to some extent, a measure of the "coatability" of a cellulose-based substrate surface, i.e. the ability to be coated with an aqueous solution composition of a gas barrier polymer. If the surface is able to absorb too much solution before drying, a thinly applied wet coating will crack and fail to form a continuous coating of the gas barrier polymer. It is therefore preferred that the Cobb 60 value is below 30 g / m 2 , for example, less than 28g / m 2 , and preferably not higher than 25g / m 2 .
[0074] The surface of the top side of the cellulose-based substrate may exhibit a Bendtsen roughness value of less than 30 ml / min and a roughness value of less than 25 g / m 2 Or lower Cobb 60 absorption value.
[0075] In one embodiment, the surface of the top side of the paper-based or cellulose-based substrate will exhibit a Gurley porosity value of greater than 1000 s / dl, such as greater than 2000 s / dl, according to Tappi T460 om-2. An advantage of a surface with low porosity is that less of the aqueous solution of the gas barrier polymer will be absorbed into the cellulose-based substrate. Since the dispersion-coated aqueous composition of the base coating may be very thin, this may be important for the internal coherence of the coating and the ability of the coating to form a smooth and uniform surface to receive further coatings or layers thereon.
[0076] Therefore, in a cellulose-based substrate suitable for coating with a thin coating of an aqueous solution composition comprising an oxygen barrier polymer, the number and size of pores in the substrate material should preferably be significantly reduced. By extensively refining the pulp used to make the substrate, the degree of fiber bonding will increase, thereby reducing the porosity. Greaseproof paper is produced by such extensive refining and has a sufficiently low porosity to provide a grease barrier.
[0077] Therefore, greaseproof paper is also considered as a potential substrate or carrier for additional gas barrier coatings. However, the resulting pulp has a high dewatering resistance, requires a long time for raw material dewatering, and the manufacturing process is costly and not conducive to repulping and recycling processes. The same is true for parchment paper, during the manufacturing process, the parchment paper obtains gelled fibers through a sulfuric acid bath, which makes the fibers difficult to dewater and repulp, and the parchment paper has an undesirable brittleness. The same is true for papers or films containing more than 50% by weight, i.e. a large part of fibril cellulose (such as MFC or NFC). The inclusion of fibrillated cellulose into a cellulose-based substrate makes it less advantageous to recover the cellulose fibers (i.e. in fiber form) from a laminate containing paper or a cellulose-based substrate in the repulping process.
[0078] According to one embodiment, the cellulose-based substrate used in the present invention may be formed from cellulose fibers comprising at least 50% by dry weight of chemical pulp, such as kraft pulp or sulfite pulp. Sulfate or sulfite pulp is used to obtain a paper that is strong enough for downstream processes such as coating at high line speeds, as well as conversion lamination and final packaging use.
[0079] Sulfate / Kraft pulp may be preferred because it is widely produced in large quantities and facilitates improved repulping in recycling and general dewatering of the fiber. Sulfite fiber typically has a higher proportion of refined fiber, which may have a slightly opposite effect, depending on how high the proportion is and the degree of refining. According to one embodiment of the present invention, Kraft pulp may therefore be preferred.
[0080] The cellulose-based substrate may be formed from cellulose fibers comprising 35-100% (eg 35-80%, such as 40-70%) softwood pulp for forming high density paper by dry weight of pulp. The remainder of the pulp composition may include hardwood fibers and some minor amounts of other fibers.
[0081] The benefits of including softwood pulp are improved paper machine runnability and beneficial strength / toughness properties for the resulting paper. A relatively high proportion of softwood pulp promotes a cellulose-based substrate having a sufficiently high density without causing dewatering problems during substrate manufacturing and enabling repulping in recycling operations. The degree of refinement of the fiber components is further selected to promote dewatering and repulpability while forming a dense paper with relatively low porosity.
[0082] Therefore, although there are some substrate papers with inherently good oxygen barrier properties, these are less preferred for the final material for other reasons, such as low recyclability (repulpability), and a major contribution to the oxygen barrier properties needs to be provided by the coating material in order to coat and adhere well to and interact well with the substrate surface.
[0083] In order to have good coating mechanical properties at high coating line speeds above 300 m / min (e.g. above 400 m / min), the cellulose-based substrate should have a tensile strength of 3 to 6 KN / m in MD (machine direction) and 1.5 to 3.5 KN / m in CD (cross direction). In the present disclosure, tensile strength is measured according to ISO 1924-3:2005. Therefore, a higher tensile strength may indicate that the paper substrate can be used to withstand web handling forces during coating and lamination operations.
[0084] The cellulose-based substrate may also have a tensile strain in the machine direction of 1.4 to 3.5% and a tensile strain in the CD direction of 2.1 to 6.0%.
[0085] The cellulose-based substrate may also have a 35 to 90 J / m 2 The tensile energy in the CD direction is 37 to 140 J / m 2 of stretching energy.
[0086] In addition, the E modulus of the cellulose-based substrate may be 9500 to 12500 MPa in the MD direction and 4000 to 7000 MPa in the CD direction.
[0087] Preferably, beneficial barrier and recyclability properties are obtained without sacrificing tensile strength and other mechanical properties.
[0088] It has previously been found that vapor deposited coatings applied to thicknesses of only nanometers (e.g., metallized coatings) first require a thin, defect-free, base-smoothing polymer coating or pre-coating to be applied to a paper or cellulose-based substrate to provide the barrier properties and / or good sheet resistance of the metallized coating. Such good performing polymers for the base coating may be selected from vinyl alcohol polymers and copolymers, which also have inherent gas barrier properties and are food safe and environmentally sustainable both in terms of recyclability and in terms of industrial coating and lamination processes. Such polymers are water-dispersible and / or soluble in water and are applied by an aqueous "dispersion coating" process or a so-called "liquid film coating" process. A polymer with a good smoothing effect is starch or a modified starch. However, in general, the gas barrier properties of starch materials are significantly lower than, for example, PVOH.
[0089] In the case of high frequency induction heat sealing, it has recently become known that starch materials work significantly better as base coatings for receiving induction sensitive metallized layers. Starch materials appear to provide better thermomechanical stability during the heat sealing operation and also have a significant smoothing effect, making the initial roughness of the substrate surface potentially less critical to the quality of subsequently applied thin barrier and metal coatings.
[0090] A starch material suitable for use in such a base coating may be an oxidized or modified starch suitable for being water soluble at cold or ambient temperatures, such as oxidized native potato starch, etc., since such cold water soluble starches do not form gels during production. An example of such a suitable starch material is Avebe from the Netherlands. or 1290.
[0091] The base coat can be applied as a single coat or in two successive thinner coats.
[0092] Other polysaccharide materials may also be used as the base coating under slightly adjusted application, coating and drying conditions. Other such conceivable materials suitable for inclusion in the base coating may be thin coatings of cellulose ether materials that are easy to be applied with dispersions or solutions. Cellulose ether materials also have smooth properties when applied to less smooth paper or paperboard surfaces, so that they can provide high-quality subsequent vapor deposition metal coatings. However, known cellulose ethers do not have oxygen barrier properties and are therefore less preferred than starch materials for base coatings. Suitable cellulose ether materials may include one or more compounds selected from the group consisting of methylcellulose, ethylcellulose, carboxymethylcellulose CMC, hydroxyethylcellulose HEC, hydroxypropylcellulose HPC, hydroxypropylmethylcellulose HPMC and sodium carboxymethylcellulose NaCMC.
[0093] The composition of the base coating may further comprise inorganic particles or fillers, such as talc, kaolin and nanoclays, such as bentonite, montmorillonite, etc. The amount of such inorganic material may be 1 wt % to 40 wt %, such as 1 wt % to 30 wt %, such as 1 wt % to 20 wt %, such as 1 wt % to 15 wt % of the composition of the base coating, based on the solid content.
[0094] The aqueous solution of the base coating composition can be uniformly applied to the top surface of the web of the cellulose-based substrate by a roller coating method to provide 0.3 g / m 2 Up to 2g / m 2 Dry weight of coating: less than 0.3g / m 2 When the starch is higher than 2 g / m 2 Or even 1.5g / m 2 When the coating is thicker, it will be more difficult to dry and more energy and time will be required to evaporate the water in the starch. 2 And more starch can achieve good smoothing effect, while 0.5g / m 2 Up to 0.8g / m 2 A coating of 100% can achieve a good balance between coating quality and cost efficiency. Generally, a thicker coating of starch material is required overall, so at least one further coating step is added after the first coating is dried.
[0095] Thus, the base coating can be applied as two partial layers in two consecutive steps with intermediate drying. When applied in two partial layers, the amount of each layer applied is suitably 0.2 g / m2 on a dry weight basis. 2 Up to 1g / m 2 , for example 0.2g / m 2 Up to 0.8g / m 2 , for example 0.5g / m 2 Up to 0.7g / m 2 , and enables a higher quality overall layer to be obtained using a smaller amount of liquid base coating material composition.
[0096] Therefore, each 0.2g / m 2 Up to 1g / m 2 Two starch partial layers are applied in an amount of 100%, but since the starch base coating provides a very good smoothness coating with only a single coating, the metal coating can be obtained with a sufficiently good quality with only one such base coating. Therefore, due to the smoothness and high quality of the metal coating applied on the starch base coating, it seems sufficient to apply only a single gas barrier coating as a top coating and still obtain very good gas barrier properties as well as good high frequency induction heat sealing capabilities.
[0097] Next, the barrier-coated cellulose substrate of the present invention comprises a step of vapor depositing a metal coating by physical vapor deposition (PVD) onto the first applied base coating obtained from an applied and dried aqueous solution of a heat-stable polymer.
[0098] In the method of the present invention, the physical vapor deposition coating is a metallized coating, preferably an aluminum metallized coating.
[0099] Such thin vapor deposited metal coatings are nanometer-thick, i.e., they have a thickness that is best measured in nanometers, e.g., 5 to 500 nm (50 to ), for example 5 to 200 nm, more for example 5 to 100 nm, for example 5 to 50 nm.
[0100] Typically, below 5 nm, the barrier properties may be too low and the metallized coating will have too high a sheet resistance for induction heating, while above 200 nm, such as at 100 nm and above, such as at 80 nm and above, such as at 50 nm and above, depending on the quality of the deposited coating, the barrier coating may be less flexible and therefore more susceptible to cracking when applied to a flexible substrate, and will also be more costly since the deposition coating speed must be reduced.
[0101] In one embodiment, considering the flexibility of the applied metallized coating and the efficiency of the coating operation, the metal deposition coating is applied to a thickness of 10nm to 200nm, such as 10nm to 150nm, such as 10nm to 100nm, such as 10nm to 95nm, such as 10nm to 80nm, such as 10nm to 50nm, which is equivalent to less than 1-3% of the aluminum metal material present in conventional thickness (e.g., 6μm-9μm) aluminum foil for packaging.
[0102] While vapor deposited metal coatings require much less metallic material than metal foils, they can only provide low levels of oxygen barrier properties at best and need to be combined with other gas barrier materials in order to provide a final laminate with adequate barrier properties. On the other hand, it can complement a gas barrier layer such as PVOH or EVOH, which does not provide water vapor barrier properties and is quite sensitive to moisture.
[0103] Other examples of vapor deposited coatings are aluminum oxide (AlO x , Al2O3) and silicon oxide (SiO x Typically, such PVD coatings will be more brittle and less suitable for incorporation into packaging materials by lamination, whereas the metallized layer, although made by PVD, may have mechanical properties more suitable for lamination.
[0104] Typically, the aluminum metallization layer also inherently has a thin surface portion comprising aluminum oxide, which is typically inherently formed at the end of the metallization coating process.
[0105] Aluminum metallized coatings can be applied by physical vapor deposition to sheet resistance values of 0.25Ω□ to 0.75Ω□, for example 0.4Ω□ to 0.6Ω□. To achieve induction heat sealing, the sheet resistance of the metallized coating should be as low as possible, but there is a practical lower limit to what is possible. The optimum level found to date is about 0.5Ω□ to 0.75Ω□.
[0106] In order for the PVD coating process to work optimally, the moisture content in the paper-based or cellulose-based substrate should be maintained between 4% and 8%. If the paper substrate becomes too dry, it may cause its longitudinal edges to curl toward each other and cause coating and handling problems in the method of the present invention. On the other hand, if the moisture content becomes too high, the vapor deposition coating operation may not work properly to provide a high-quality coating.
[0107] In one embodiment, the aluminum metallization layer is applied to an optical density (OD) of 1.8 or higher, such as from 1.8 to 4, such as from 2 to 3.5, such as from 2.5 to 3.5. At an optical density below 1.8, the barrier properties of the metallized film may be too low, and at an OD below 2.0, the sheet resistance may be too high. At an OD above 4, the deposited metal layer may be more sensitive to mechanical stress and less flexible, forming cracks or defects, which in turn may impair oxygen barrier properties as well as induction heat sealing properties.
[0108] In some embodiments, the metal coating may be deposited as two consecutive deposited coats to improve quality and flexibility.
[0109] The optical density is measured in production by a densitometer, i.e. an instrument using the principle of diffuse light transmission (e.g. from Macbeth, Tobias or similar). This instrument is suitable for measuring the optical density values of metallized films coated with aluminum. The accuracy and precision of the measurement are very high, about + / - 0.2 OD and about + / - 0.01 OD, respectively, within the measuring range of 0 to 6.60 OD.
[0110] In laboratory measurements, a spectrophotometer can alternatively measure the light transmittance across the entire visible spectrum (380-800 nm). According to the formula OD = -log 10 (I1 / I0), the optical density is calculated based on the transmittance (T) value at 560nm, and the obtained value is equally accurate (+ / -0.2OD) and comparable to the transmittance densitometer value.
[0111] The metallized coating is also coated with a thin aqueous solution composition comprising a gas barrier polymer. The gas barrier polymer also needs to exhibit a certain thermal stability during induction heat sealing so that it does not melt or degrade, while the adjacent heat-sealable material layer should be the same. Therefore, the melting point of the gas barrier polymer can be higher than the melting point of the material to be melted and heat-sealed. The gas barrier polymer of the aqueous solution composition for the top coating can be suitably a polymer or copolymer based on vinyl alcohol monomer, which is for example selected from polyvinyl alcohol (PVOH), ethylene vinyl alcohol copolymer (EVOH) and modified PVOH and EVOH copolymers that can form an aqueous solution. In some cases, this polymer is modified, for example, by adding carboxylic acid functional groups.
[0112] In one embodiment, the water soluble gas barrier polymer is PVOH, such as PVOH from Kuraray Type PVOH, which provides good film-forming properties, gas barrier properties, cost-effectiveness, food compatibility and odor barrier properties.
[0113] In another embodiment, the gas barrier polymer is a water-soluble EVOH having a low ethylene monomer content, such as EVOH from Kuraray. Type EVOH. The advantage of using EVOH polymer as a gas barrier material is that the ethylene content supports moisture resistance, so that the oxygen barrier properties are better maintained even at higher relative humidity (e.g. 80% RH). This is especially suitable for packaging of oxygen-sensitive liquids, such as paperboard laminate packaging for liquid foods.
[0114] Conventional EVOH polymers are usually used for extrusion and cannot be dispersed or dissolved in aqueous media to produce 4g / m 2 Barrier films coated with thin liquid films of or below. Water-soluble EVOH contains higher amounts of vinyl alcohol monomer units to have water dispersibility, and its performance is as close as possible to liquid film coating grade PVOH. In addition, it is shown that this water-soluble EVOH has a melting point higher than that of the material layer to be heat-sealed, and therefore has sufficient thermal stability to support the metallized coating and withstand induction heat sealing operations.
[0115] On the other hand, an extruded EVOH layer is not a replacement for liquid film coated EVOH, since it is inherently less similar in properties to PVOH than EVOH grades for dispersion / solution coating, and it cannot be applied in an efficient manner by melt extrusion coating or melt extrusion lamination to obtain sufficient adhesion to adjacent layers. Melt coextrusion coating of polyethylene and vinyl tie layer polymers is technically difficult to carry out due to differences and incompatibilities in melt viscosity.
[0116] Gas barrier compositions based on PVOH perform best when the PVOH has a saponification degree of at least 98% (preferably at least 99%), but PVOH with a lower degree of saponification will also provide oxygen barrier properties. The most advantageous PVOH quality and grade for the process of the present invention is 6-98.
[0117] In another embodiment, PVOH can be 15-99.
[0118] In yet another embodiment, the PVOH may be 6-96, although this grade may offer slightly lower oxygen barrier properties.
[0119] The EVOH grade suitable for coating in the method of the present invention can be 4104AQ, which has 6-98 similar coatability, and HR-3010, which has 15-99 Similar coatability.
[0120] Possible additives in the barrier topcoat composition may be polymers or compounds with functional carboxylic acid groups, the purpose of which is to improve the water vapor and oxygen barrier properties of the PVOH topcoat, in particular to improve the adhesion of the topcoat to the metallized coating on the surface of the coated paper substrate. Suitably, such polymers with functional carboxylic acid groups are selected from ethylene acrylic acid copolymers (EAA) and ethylene methacrylic acid copolymers (EMAA) or mixtures thereof. EAA or EMAA copolymers may be included in the barrier topcoat in an amount of 1 wt % to 49 wt %, such as 1 wt % to 40 wt %, such as 1 wt %-35 wt %, such as 1 wt % to 30 wt %, such as 1 wt % to 25 wt %, such as 1 wt % to 20 wt %, such as 1 wt % to 15 wt %, based on the dry coating weight.
[0121] In one embodiment, the top coating can be applied as two consecutive layers, wherein the first coating comprises a higher proportion of EAA adhesive polymer, the remainder being PVOH, and the second coating comprises a major proportion of PVOH, or comprises only PVOH. Thus, the top coating can provide good adhesion to the metallized surface and good gas barrier properties at an optimal level.
[0122] In one embodiment, the barrier layer mixture can consist essentially of PVOH, EAA, and an inorganic laminar compound, e.g., containing from about 1 wt % to about 10 wt % of an inorganic laminar compound, such as talc, kaolin, or exfoliated nanoclay particles, such as bentonite, based on dry coating weight.
[0123] Thus, while it is more preferred to use a barrier pre-coat made from a pure PVOH or EVOH composition, advantageous results may also be obtained with a gas barrier pre-coat containing other additives as described above.
[0124] The aqueous solution of the gas barrier polymer of the top coating layer may be uniformly applied to the surface of the top side of the web of the metallized cellulose-based substrate by roller coating to provide a dry weight of 0.5 to 2 g / m 2 The coating is preferably 0.5 to 1.5 g / m 2 Coating. Less than 0.5g / m 2 When the gas barrier performance is higher than 2g / m 2 When the coating is applied to packaging laminates, it will not be cost-effective due to the high energy costs and the short time available for evaporation of water (due to the high coating line speed). 2 and above to achieve a recognizable oxygen barrier level, and between 0.5 and 2 g / m 2 A good balance between barrier properties, coating quality and cost is achieved in a coating of the desired thickness. Typically, a thicker gas barrier polymer coating is required overall, so at least one further coating step is added after the drying of the first coating layer is complete.
[0125] Thus, the thermally stable gas barrier top coating can be applied in two consecutive steps in the form of two partial layers with drying in between. The two partial layers can have different compositions or mixing ratios of the vinyl alcohol-based polymer and the other polymers and additives. Thus, when applied as two partial layers, a suitable application amount for each partial layer is 0.2 g / m by dry weight. 2 Up to 1.5g / m 2 , for example 0.2g / m 2 Up to 1g / m 2 , and allows a higher quality overall layer to be obtained from a lower amount of liquid gas barrier composition. Thus, the two PVOH partial layers can be made at 0.25 g / m 2 Up to 1g / m 2 , for example 0.3g / m 2 Up to 0.8g / m 2 , for example 0.5g / m 2 Up to 0.8g / m 2 amount applied.
[0126] The starch base coating can also be applied in the form of two such consecutive coats with drying in between, but since the starch base coating provides a very good smooth coating with only a single coat, the metal coating can be of sufficiently good quality with only one such base coating. In addition, due to the smoothness and high quality of the metal coating applied on the starch base coating, it seems that applying only a single gas barrier coating as a top coat is sufficient to obtain very good gas barrier properties and high frequency induction heat sealing capability.
[0127] The thermally stable gas barrier top coating composition may also include a small amount (e.g., 1 wt % to about 20 wt %, e.g., 1 wt % to about 15 wt % based on the dry coating weight) of an inorganic layered compound, such as talc, kaolin, or exfoliated nanoclay particles, such as bentonite. In this case, the barrier layer may include about 99 wt % to about 90 wt % of the polymer based on the dry coating weight.
[0128] The amount of wet coating applied can be about ten times higher than the solid target coating applied and dried, so the amount of the corresponding starch or PVOH wet coating applied is about 5 to about 20 g / m 2 , for example 5 to about 10 g / m 2 , which therefore explains the need for evaporation of considerable weight of water in the drying step at high coating speeds. It is important not to allow excessive moisture to remain on the coated substrate or to be absorbed by the substrate, as this moisture may interfere with any subsequent steps in the subsequent coating and lamination operations and cause defects in the applied barrier coating, thereby compromising the coating quality and ultimately reducing the beneficial properties provided by the barrier-coated substrate.
[0129] Industrially feasible (i.e., high speed) methods suitable for applying the base coating and aqueous polymer solution composition of the thermally stable gas barrier top coating of the present invention can be generally any suitable wet roll coating method, such as rotogravure roll coating, smooth roll coating, and reverse roll or gravure coating. In an advantageous embodiment of the method of the present invention, the aqueous polymer composition is applied by reverse gravure coating. The reverse direction of the gravure coating process has been shown to be more conducive to smoothing the coating surface compared to forward gravure coating, which is more like a printing process that prints the gas barrier polymer onto a surface rather than a full coating process.
[0130] The solid content of the water-soluble polymer should be 5 to 15% by weight to be suitable for the roller coating application method, and can be adjusted to a suitable solid content according to the choice of polymer and the coating speed. The solid content in the method of the present invention is more preferably 7 to 13% by weight, such as 9 to 13% by weight, such as preferably 10 to 12.5% by weight. It has been proven that when the solid content is above 10%, the best quality coating can be obtained by the reverse gravure coating method, that is, the coating is uniform, smooth and substantially free of defects.
[0131] The viscosity of the aqueous solution of the starch-based coating or PVOH gas barrier polymer to be applied should be from 10 to 120 mPa*s, such as from 50 to 100 mPa*s. This allows the gas barrier solution to be optimally picked up by the gravure roll and further transferred onto the substrate surface at high coating line speeds above 300 m / min, such as above 400 m / min, such as above 600 m / min.
[0132] The gas barrier composition may further contain additives such as dispersion stabilizers, etc., preferably in an amount of no more than about 1 wt % based on the dry coating. The total dry content of the composition is preferably 5 to 15 wt %, more preferably 7 to 12 wt %.
[0133] The aqueous solution composition of the base coating or thermally stable gas barrier top coating may be heated and applied at a temperature of 60 degrees C to 80 degrees C. By heating to such high temperatures, the risk of foam bubbles forming in the coating is reduced.
[0134] To further reduce bubble or foam formation in the aqueous polymer solution, a defoaming additive may be added. A preferred defoaming agent is n-octanol, which is both food safe and has been shown to provide better results than other tested agents at low amounts (e.g., at low amounts of 0.01 to 0.1 wt % of the solution, such as at low amounts of about 0.05 wt % of the solution). It is noted that other tested agents deteriorate the PVOH, causing them to increase the OTR of the applied and dried PVOH coating.
[0135] Continued drying at low temperatures only is advantageous because wet coatings of aqueous gas barrier polymer solutions are very thin and may be damaged by excessive application of heat.
[0136] The drying step can be carried out by a hot air dryer, which also allows the water to evaporate and be blown away from the surface of the substrate by air convection. As the substrate passes through the dryer, the substrate temperature can be kept constant at a temperature below 95° C., such as below 85° C., such as from 75° C. to 85° C., such as about 80° C. If desired, at high line speeds, drying can be partially assisted by radiant heat from infrared IR lamps combined with hot air convection drying.
[0137] The more water is added to a wet applied coating, the more water evaporates in the dryer at high line speeds. How high a solids content is possible in a waterborne coating to achieve only 1-2 g / m 2 There is a balance between the drying of thin coatings and the length of the dryer section. The drying speed cannot be too fast, as there is a risk of skinning, nor too slow, as too high a paper absorption can lead to reduced surface film thickness and / or cracked (defective) coatings. Therefore, the evaporation of water should be controlled to avoid excessive substrate surface temperatures and skinning.
[0138] This balance setup may be unique to each coating line and / paper / coating combination.
[0139] The paper or cellulose-based substrate coated with a barrier layer obtained according to the process of the present invention provides excellent low OTR and surprisingly also shows resistance to degradation of the low OTR at high relative humidity levels of 80% (RH) (i.e. no increase or very low increase), despite the gas barrier coating being located inside the metallized coating in the laminated packaging material, making it more susceptible to water vapor migration from liquid or wet products in the filled packaging container. Therefore, it unexpectedly proves to be very suitable for lamination into laminated packaging materials and further suitable for folding, forming and sealing operations of such laminated materials into packages.
[0140] The laminated packaging material comprising a cellulose-based substrate coated with a barrier layer also includes a first outermost protective material layer and a second innermost liquid-tight heat-sealable material layer. The second innermost liquid-tight heat-sealable material layer may include a thermoplastic polymer, such as a polyolefin polymer or be made of a polyolefin polymer. The first outermost protective material layer may be transparent so that the printed decorative pattern outside the main body layer is visible. It may also include a thermoplastic polymer, such as a polyolefin polymer or be made of a polyolefin polymer.
[0141] The carton-based laminated packaging material for liquid food packaging may also include a main body layer of paper or paperboard, a first outermost protective material layer, a second innermost liquid-tight heat-sealable material layer, and the paper or cellulose-based substrate coated with a barrier layer, wherein the paper or cellulose-based substrate coated with a barrier layer is arranged on the inner side of the main body layer of paper or paperboard, toward the interior of a packaging container made of the packaging material, and between the main body layer and the second innermost liquid-tight heat-sealable material layer.
[0142] In one embodiment, the paperboard-based laminated packaging material may include a body layer of paper or paperboard, a first outermost liquid-tight heat-sealable polyolefin layer, a second innermost liquid-tight heat-sealable polyolefin layer, and the paper or cellulose-based substrate coated with a barrier layer, wherein the paper or cellulose-based substrate coated with the barrier layer is arranged on the inner side of the paper or paperboard body layer, toward the interior of a packaging container made of the packaging material, and between the body layer and the innermost liquid-tight heat-sealable polyolefin layer.
[0143] The paper or paperboard main body layer used in the present invention generally has a thickness of about 70 μm to about 600 μm, and a weight of about 65 g / m 2 -500 g / m 2 , for example 100g / m 2 -400 g / m 2 , preferably about 200g / m 2 -300g / m 2 The surface weight of the packaging material may be conventional paper or paperboard of suitable packaging quality.
[0144] If the resulting laminate is to be used as a bladder-like packaging, thinner paper layers may be used as the barrier-coated paper substrate and bulk layer, which then together provide the bulk strength or stability of the paper laminate. In this case, the additional "bulk" paper has a grammage of 40 g / m 2 Up to 64g / m 2 , for example 40g / m 2 Up to 55g / m 2 , and the paper substrate coated with the barrier layer can have a grammage of 40g / m 2 Up to 55g / m 2 .
[0145] For low-cost aseptic, long-term packaging of liquid foods, thinner packaging laminates with thinner paper core layers can be used. Packaging containers made from such packaging laminates are not folded and are more like pillow-shaped soft bags. Paper suitable for pouch packaging typically has a density of about 50 to about 140 g / m 2 , preferably about 70 to about 120 g / m 2 , more preferably 70 to about 110 g / m 2 Since the barrier-coated paper-based or cellulose-based substrate of the method of the present invention itself can bring a certain stability to the laminated material, the paper layer corresponding to the "body" layer can be thinner and interact with the barrier-coated cellulose-based substrate through interlayer interaction, thereby still producing a laminated packaging material with full desired mechanical properties.
[0146] The paper or cellulose-based substrate coated with the barrier layer may be bonded to the bulk layer via an intermediate adhesive or thermoplastic polymer bonding layer, thereby bonding the uncoated surface of the paper coated with the barrier layer to the bulk layer. According to one embodiment, the bonding layer is a polyolefin layer comprising mainly ethylene monomer units, such as, in particular, a polyethylene-based polyolefin copolymer or blend layer. The bonding layer bonds the bulk layer to the paper or cellulose-based substrate coated with the barrier layer by melt extrusion laminating the bonding polymer layer between the bulk layer web and the cellulose-based substrate web, and simultaneously pressing the three layers together as they advance through the lamination roll nip, thereby providing a laminated structure by extrusion lamination.
[0147] In another embodiment, the cellulose-based substrate coated with the barrier layer can be bonded to the bulk layer by wet application of an aqueous dispersion of a tacky composition comprising a tacky polymer adhesive to one of the surfaces of the webs to be laminated and pressing the two paper webs together as they advance through the nip of the laminating rollers, thereby providing a laminated structure by wet lamination. During the subsequent lamination process, the moisture of the aqueous tacky composition is absorbed into the fibrous cellulose network of the two cellulose-based layers and partially evaporates over time. Therefore, no forced drying step is required.
[0148] The aqueous tacky polymer binder may be selected from the group consisting of acrylic polymers and copolymers, starch, starch derivatives, cellulose and polysaccharide derivatives, polymers and copolymers of vinyl acetate and vinyl alcohol, and copolymers of styrene-acrylic latex or styrene-butadiene latex. For best environmental and sustainability properties, tacky binders derived from plant or non-fossil sources are preferred.
[0149] Suitable thermoplastics for the outermost heat-sealable liquid-tight layer and the innermost heat-sealable liquid-tight layer are polyolefins, such as polyethylene and polypropylene homopolymers or copolymers, preferably polyethylene, more preferably polyethylene selected from low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), single-site catalyst metallocene polyethylene (m-LLDPE) and mixtures or copolymers thereof. According to one embodiment, the first outermost protective liquid-tight layer is LDPE, and the second innermost heat-sealable liquid-tight layer is a blended composition of m-LLDPE and LDPE to obtain optimal lamination and heat-sealing properties.
[0150] The same thermoplastic polyolefin-based materials (particularly polyethylene) listed for the first outermost layer and the second innermost layer are also suitable as adhesive layers inside the laminate, i.e., adhesive layers between the bulk or core layer (e.g., paper or paperboard) and the barrier film or sheet. In one embodiment, the thermoplastic internal adhesive layer can be a polyolefin layer, such as a polyethylene layer, such as a low-density polyethylene (LDPE) layer.
[0151] In another embodiment, the second innermost liquid-tight heat-sealable polyolefin layer is a preformed film comprising the same or similar polyolefin as described above, i.e. LDPE, LLDPE and / or m-LLDPE, such as a biaxially oriented film comprising at least one layer of predominantly LLDPE polymer to improve the robustness of the mechanical properties of the packaging material. Due to the manufacturing process in the film blowing and film casting operations, and the optional subsequent film orientation operation step, the polymer of such a film acquires different properties than a (co)extrusion coated polyolefin layer might acquire. Such a preformed, preferably oriented polymer film would contribute significantly to the mechanical robustness of the laminated packaging material and the mechanical strength and packaging integrity of the packaging container formed and filled with the laminated packaging material.
[0152] According to an alternative embodiment, a suitable adhesive or tie layer inside the laminate (such as, for example, between the bulk layer or core layer and the cellulose-based substrate coated with a barrier layer or between the outer heat-sealable layer and the paper substrate coated with a barrier layer) is also a so-called adhesive thermoplastic polymer (such as a modified polyolefin), which is mainly based on LDPE or LLDPE copolymers or graft copolymers with monomer units containing functional groups (such as carboxyl or glycidyl functional groups) (such as (meth)acrylic acid monomers or maleic anhydride (MAH) monomers) (i.e. ethylene acrylic acid copolymer (EAA) or ethylene methacrylic acid copolymer (EMAA)), ethylene-glycidyl (meth)acrylate copolymer (EG(M)A) or MAH-grafted polyethylene (MAH-g-PE). Another example of such a modified polymer or adhesive polymer is a so-called ionomer or ionomer polymer. Preferably, the modified polyolefin is an ethylene acrylic acid copolymer (EAA) or an ethylene methacrylic acid copolymer (EMAA).
[0153] The laminated packaging material produced according to the above method provides good integrity when converted into filled packaging containers by good adhesion and interaction between adjacent layers within the laminate structure and by providing good quality gas barrier coatings and vapor deposited barrier coatings. Especially for the packaging of liquids and wet foods, an important conclusion is that the interlayer adhesion within the laminated packaging material as well as the oxygen barrier properties are maintained under wet packaging conditions.
[0154] According to a further embodiment, a packaging container formed from a laminated packaging material may be partially sealed, filled with a liquid or semi-liquid food and subsequently sealed by sealing the packaging material to itself (optionally in combination with a plastic opening or top portion of the package).
[0155] In summary, the barrier coated cellulose based substrate as defined in the present invention and the laminated packaging material comprising the barrier coated cellulose based substrate can achieve a robust and reliable packaging for liquid food packaging for long shelf life and storage due to the improved barrier properties provided. The laminated packaging material structure is more suitable for forming folded and formed packages, both because of the improved adhesion between the substrate and the barrier material coating and because of the improved contribution of the barrier coating substrate itself to the gas barrier properties, which may also be due to the good cohesion and adhesion of the barrier coating to the barrier coated cellulose based substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0156] The preferred embodiments of the present invention will be described below with reference to the accompanying drawings, in which:
[0157] Figure 1 Schematically shows an example of a cross section of a cellulose-based substrate coated with a gas and water vapor barrier layer produced by the method according to the invention,
[0158] Figure 2 A schematic cross-sectional view of a laminated packaging material is shown, the laminated packaging material comprising Figure 1 A cellulose-based substrate coated with a barrier layer,
[0159] Figure 3a A method for applying a gas barrier coating composition dispersion onto a cellulose-based substrate is schematically shown.
[0160] Figure 3b Schematically showing a method for melt (co)extrusion coating a thermoplastic heat-sealable and liquid-tight polymer layer onto a web substrate to form the innermost and outermost layers of the packaging laminate of the present invention,
[0161] Figure 4 A schematic diagram of an apparatus for physical vapor deposition (PVD) coating on a coil substrate by using a solid metal evaporator is shown,
[0162] Figure 5a , 5b 5c and 5d show typical examples of packaging containers produced from the laminated packaging material according to the present invention,
[0163] Figure 6 shows the principles of how such packaging containers can be manufactured from packaging laminates in a continuous, roll-fed, form, fill and seal process, and
[0164] Figure 7a a cross section of a transversely sealed packaging material tube at the overlap region of a longitudinal seal LS formed by folding the packaging material into a tube, and
[0165] Figure 7b The top view shows how strong light passes through Figure 7a Thinning or defects in the metallized coating in the LS area of the formed and sealed packaging material are shown. DETAILED DESCRIPTION
[0166] As mentioned in the introduction, Patent Publication No. WO2011 / 003565A1 discloses a laminated non-aluminum foil packaging material comprising a kraft paper substrate coated with a base layer and metallized for induction heat sealing the innermost thermoplastic polymer layer towards the inside of the packaging container. It particularly recommends PVOH and additional nanoclay particles in an aqueous composition as a base coating to obtain good gas barrier properties, and further applies an aluminum metallized PVD deposited coating thereon. In order for the base coating to be well used for induction heat sealing of the laminated packaging material, the polymer or adhesive of the base coating has a higher melting point than the innermost heat-sealable polymer layer. Many equivalent or similar base coating polymers with induction heat durability are listed, namely starch, other polysaccharides, PVOH, water-dispersible EVOH, polyvinylidene chloride.
[0167] From recent research it has emerged that the PVOH base coating may not be the best choice for induction heat sealing in the examples listed after all, the current hypothesis being that PVOH may not be completely thermally stable under the harsh induction heating conditions such that the metallized layer does not remain intact enough to achieve a defect-free and tight seal. It has further been found that if starch is used as the metallized base coating instead, the power "window" within which thicker materials can also be induction sealable can be expanded, i.e., good induction heat seals can be made at both lower and higher power settings. Example Example 1
[0168] Different base coating materials were applied to cellulose-based substrates and tested for their ability to be heat-sealed by high-frequency induction heat sealing as well as their oxygen barrier properties.
[0169] Two different samples of cellulose-based substrates coated with a barrier layer were prepared. In the first sample, PVOH (i.e., 6-98) The base coating is applied to a paper substrate having a density of about 950 kg / m 3 , weight is about 40g / m 2 , surface roughness is less than 200ml / min Bendtsen. In the first sample, the PVOH base coating is about 0.7g / m 2 Two consecutive coatings of are applied to the substrate paper.
[0170] In the second sample, a cold water soluble starch base coating was applied as about 0.5-0.6 g / m 2 Two consecutive coatings of are applied to the same paper substrate.
[0171] The two base coated paper substrate samples were further metallized by physical vapor deposition to a sheet resistivity of about 0.5 Ω□ (ohm / square) of the metallized coating and subsequently laminated into a laminate structure having the following main structure:
[0172] / / LDPE outer side (12g / m 2 ) / paperboard 80mN / adhesive layer mixture LDPE+mLLDPE (15g / m 2 ) / Barrier coated Paper substrate / Adhesive polymer EAA (6g / m 2 ) / LDPE(13g / m 2 ) / Biaxially oriented LLDPE film (18μm) / /
[0173] When the laminated packaging material is formed into a tubular packaging container, as described in the above introduction and in combination with the following Figure 6 As described, the longitudinal edges of the coils are placed in succession to form overlapping longitudinal seal areas, thereby connecting along the formed tube at the longitudinal seal "LS" area by applying heat and pressure simultaneously. When heat is applied through the metallized aluminum layer by high frequency induction heating, small defects in the form of tiny holes or inhomogeneities may appear in the metallized coating.
[0174] Furthermore, when the tube is re-formed into individual packages, the tube is sealed transversely and the resulting "pillow-shaped" packages are cut from the tube. Since the longitudinal seal further involves the transverse seal (intersecting the transverse seal), a double overlap region "LS-TS" is created, which is prone to further defects during the heat sealing operation due to the greater thickness of the overlapping material in this area. Here, defect occurrence can be particularly relevant at the longitudinal edges of the overlapping material, where the edges of the thicker paperboard cause significant stresses on the adjacent and surrounding material layers and coatings, which are much thinner than the paperboard. By applying the induced current and heat as well as the pressure, the stresses are intensified so that defects mainly appear in the metallized coating at the edge location of the paperboard.
[0175] Small marks, thinning or crack initiations in the metallized coating at the longitudinal edge locations of the laminated packaging material can be seen as lighted marks by exposing the packaging material in that area to a backlight, for example by placing the flat packaging material over a light box with a strong light.
[0176] Figure 7aA cross section of the transverse seal area of a folded tube including a longitudinal overlap seal on one side is shown. Thus, it is shown how the longitudinal edges 71, 72 overlap each other, as well as the most sensitive positions 73, 74 where such light marks may form in the metal coating at the transverse seal in the LS (longitudinal seal) area, i.e. at the LS-TS area. It is also shown how a longitudinal flat polymer sealing strip 75 is arranged and sealed to the inner polymer layer of the packaging material along one of the edges, i.e. the so-called "LS-SA" (meaning LS strip applied) edge 73, to cover the originally exposed edge 73 of the cut material of the inner overlapping edge of the tube. Since the tube is transversely sealed, the side with the LS overlap is sealed to the opposite side of the tube 76. Therefore, the folded edge of the transversely sealed tube is outside the figure and is not shown here.
[0177] therefore, Figure 7b Such light marks 77, 78 are shown as being visible and relatively large when viewing the flat material under strong backlighting, corresponding to Figure 7a Even though these marks are much smaller, they can have a negative impact on the quality of the heat seal, as they interfere with the induction heating process and can result in defects or uneven sealing areas. The quality of the LS-TS area can be visually checked by backlighting for the presence of such marks.
[0178] In the test apparatus, two laminated sample structures are heat sealed to narrow strips of material respectively to simulate the stress of the laminated material at the overlap seal in the longitudinal sealing area (LS) under the heat sealing operation conditions of the filling machine.
[0179] The laminate samples tested in this way were exposed to different high-frequency induction power settings of 1500W, 2000W and 2500W at a sealing pressure of 12kN for 200 milliseconds. The highest power setting of 2500W exceeded the actual conditions, thereby further stressing the material and the sealing operation. The heat-sealable polymer material strips had three different thicknesses and were applied and heat-sealed to the inside of each material sample to evaluate the robustness of the material when heat-sealed at each of the three different power levels. The thickness of the strips varied between 0.25 mm and 0.5 mm.
[0180] To evaluate the seal and material quality in the most challenging portion of heat-sealed packaging materials, the LS-TS region, the seal area was visually inspected and the number of visible optical marks recorded at different power settings of the inductor used to heat to seal the transverse seal. The number of visually identifiable marks produced in the metallized coating at the LS overlap seal at different power levels is recorded in Table 1. For any given material, higher power levels and higher material thicknesses generally produced at least some visible marks, and the number of marks in the metallized coating was greater than at lower powers and lower thicknesses.
[0181] The two laminated sample structures were also folded into shape, filled and sealed in a filling machine into a water-filled packaging container. The oxygen transmission rate of the packaging (filled, empty and dry) was measured according to ASTM F1307-14 at 0.2 atmospheres (ambient air contains 21% oxygen). The unit is cm 3 / packaging / 24h, conditions are 23℃ and 50%RH.
[0182] For OTR measurements, the package is mounted on a special stand and the inside of the package is filled with nitrogen. The outside of the package is exposed to the environment surrounding the instrument. As oxygen permeates through the package into the nitrogen carrier gas, it is transported to the coulometric sensor. The sensor reads how much oxygen has leaked into the nitrogen inside the package.
[0183] Table 1 shows the number of visible marks observed in the LS-TS area of packages made from laminated samples of the above-described cellulose-based substrates coated with a barrier layer and the oxygen transmission rate of the packages. Table 1
[0184] The packaging produced according to Comparative Example 1 has better oxygen barrier properties, and the measured oxygen permeability is higher (i.e., the barrier to oxygen permeation is lower) for the barrier coating sample with only starch base coating. On the other hand, the laminate sample according to Example 1 produces less marking in the metallized coating during the transverse induction heat sealing operation. It is concluded from these results that starch as a base coating provides better stability during the stage of applying heat to seal the inner polymer, especially in sensitive areas of the thin metallized coating that are more prone to marking. However, from a gas barrier point of view, PVOH is preferred over starch. Example 2
[0185] To further explore the opportunity, an experiment was conducted in which different barrier coating configurations were further tested for their ability to be heat sealed by high frequency induction and for oxygen barrier properties, applied to the same cellulose-based substrate as used in Example 1, and with approximately the same number and thickness of coatings as in Example 1.
[0186] Therefore, six different configurations of barrier coatings were applied to paper substrates.
[0187] Therefore, the barrier-coated papers were each laminated into a laminate structure having the following main structure: / / LDPE exterior (12g / m 2 ) / paperboard 80mN / adhesive layer mixture LDPE+mLLDPE(15 g / m 2 ) / paper substrate coated with barrier layer / adhesive polymer EAA (6g / m 2 ) / LDPE(13g / m 2 ) / Biaxially oriented LLDPE film (18μm) / /
[0188] The six laminate samples consisted of the following barrier-coated paper substrate materials:
[0189] Comparative Sample 2: Barrier coated paper with two continuous 6-98 PVOH base coating, and is substantially the same as Comparative Sample 1 in Table 1.
[0190] Comparative Sample 3: Same as Comparative Sample 2, but with three consecutive 6-98 PVOH base coating (each layer is the same thickness, so the total thickness is thicker PVOH).
[0191] Comparative Sample 4: Same as Comparative Sample 3, but the first base coating has the same thickness (0.7 g / m 2 ) PVOH coating, the other two coatings are starch, and the coating amount is about 0.5-0.6g / m 2 .
[0192] Comparative Sample 5: Same as Comparative Sample 4, but the two first base coatings are of the same thickness (0.7 g / m 2 ) of PVOH coating.
[0193] Comparative Sample 6: Essentially the same as Sample 1 in Table 1, but with two consecutive PVOH coatings on the other side of the paper substrate, with the same grade and amount as the other comparative examples above.
[0194] Sample 2: Same as Sample 1 in Table 1, but with a single PVOH coating as a top coat on top of the metallized coating, with the same grade and amount (0.7 g / m 2 ).
[0195] The laminated sample structure was folded, filled and sealed into a water-filled packaging container. The LS-TS and oxygen transmission rate of the empty package were evaluated in the same manner as in Table 1.
[0196] The oxygen transmission rate of the package (filled, emptied and dried) is measured at 0.2 atm (ambient air contains 21% oxygen) according to ASTM F1307-14. The unit is cm 3 / packaging / 24h, conditions are 23°C and 50% RH.
[0197] For OTR measurements, the package is mounted on a special stand; the inside of the package is filled with nitrogen; and the outside of the package is exposed to the environment surrounding the instrument. As oxygen permeates through the package into the nitrogen carrier gas, it is transported to the coulometer sensor. The sensor reads how much oxygen has leaked into the nitrogen inside the package.
[0198] The oxygen transmission rate values and the number of visible marks in the LS-TS area in the tested samples obtained from three different power settings are shown in Table 2. Table 2
[0199] Of the different variations in adding PVOH gas barrier material to the barrier coating configurations in Samples 1-6 of Table 2 for improved oxygen barrier properties, the configuration containing a PVOH top coating appears to work best and surprisingly also further improves HFIH sealability to withstand higher power and induced thermal stresses.
[0200] It can be concluded that only one laminate sample (i.e., Sample 2) actually achieved good barrier properties and good heat sealing in the LS-TS region, which is very important for barrier and sealing performance of rectangular, folding, carton laminated packaging. It is believed that a smooth and relatively more thermally stable material (such as starch) base coating provides a better foundation to achieve a high quality and high performance barrier layer structure in terms of both induction heat sealing and oxygen barrier performance. Example 3
[0201] In order to detect small pinholes, weakenings and defects formed in one or more polymer layers inside the metallized coating (i.e. on the side facing the filled product) during the heat sealing process, a method is used: a high voltage is applied and increased between electrodes arranged on an area inside the laminated packaging material and the conductive layer (i.e. the metallized coating of aluminum). When there is a slight sign of a weakness, hole or crack in the polymer layer, such as a "thinning" (i.e. an area or site that is only thinly covered by a thin polymer material) such that contact between the filled liquid or wet product and the metallized coating may occur, a recordable "dielectric breakdown" will occur between the electrode and the metallized coating, i.e. a voltage interruption, which may also be visible as a light arc between the electrode and the metal coating. The voltage is gradually increased from an initial lower value to a higher predetermined value, and there will be a value in between that will cause dielectric breakdown, which can be recorded by an oscilloscope. Alternatively, the material "thinning" or weakness can be detected by detecting a "light spark" through the weakness in the polymer layer by some kind of photodetector. The gradual increase in voltage will stress the metallized coating and adjacent layers in the laminate, so that if the material is thinned and further damaged by the voltage, the voltage will be interrupted more quickly (when a lower voltage is applied). In this way, very small areas of thin material or small weaknesses can also be observed.
[0202] Thus, this rising high pressure (RHV) method can be used to detect weaknesses in the polymer layer in any area of the packaging material, for example along the longitudinal seal LS area.
[0203] International Patent Application No. WO2012 / 091661A1 describes and discloses a RHV detection method for different areas of similar packaging materials (with a thicker aluminum foil conductive layer), and further illustrates the principle.
[0204] Therefore, in order to assess the quality of the polymer coating in the LS region outside the LS-TS region and detect defects therein, the RHV test method was used and if the voltage was found to be high enough when the interruption occurred, the power setting was considered more likely to be actually suitable for high frequency induction heat sealing of the test material. In this way, a window from the lowest to the highest possible power setting could be explored and verified under which satisfactory seal quality and seal strength could be achieved without forming defects in the internal polymer material or metallized coating. Table 3
[0205] In evaluating the RHV results, a scale of 1-3 was used to explore feasible power settings and induction heat sealing operating windows, where
[0206] "1" means that the RHV value at dielectric breakdown is rarely lower than about 2kVolt,
[0207] "2" means that the RHV was not measured because the material concept was excluded for other reasons.
[0208] "3" indicates that the RHV value at dielectric breakdown is usually less than 2kVolt.
[0209] Each heat seal power setting, where the RHV is rated as "1", i.e., there are fewer early (low) interruptions in the voltage, indicating fewer weak spots in the heat seal and inner polymer layer material, will help determine the "power window" for heat sealing of the tested material. If the heat seal power window is determined to be wider, i.e., encompasses a wider range of power settings within which the tested packaging material achieves a rating of 1 in the RHV test, then the heat seal process using that particular material will be more robust around the predetermined power setting of the fill and seal machine system. Therefore, this assessment of the width of the heat seal power window can indicate the "heat seal ability" of the material at different sealing areas of the package. The width of the power window (in units of power in Watts) is provided for the different sealing areas LS, TS and SA areas. The SA area represents the LS edge area to which the heat sealable polymer strip is applied to provide liquid tightness inside the package relative to the filled liquid product, such as Figure 7a shown.
[0210] From the results in Table 3, it can be seen that only Sample 2 provides an induction heat sealing power window in the transverse sealing operation, and it is also a fairly wide window. In addition, compared with the control sample, the packaging material of Sample 2 provides a wider window in terms of LS and SA high-frequency induction heat sealing.
[0211] In addition, regarding the attached drawings:
[0212] Figure 1 In FIG. 1 , an embodiment of a cellulose-based substrate 10 coated with a barrier layer prepared by the method of the present invention is shown in cross section. The cellulose-based substrate 11 is a cellulose-based substrate having a density greater than 900 kg / m 3 , weight is about 40g / m 2 , the top surface roughness Bendtsen value is less than 30ml / min and the Cobb 60 value is less than 25g / m 2 of paper, and having starch (such as Avebe's ) Base coating 12, which is applied in the form of an aqueous wet coating composition and then dried by heating at 60 to 95 degrees Celsius to evaporate the water in the wet-applied coating. The starch is applied in the form of two consecutive wet coatings with drying in between, each layer at about 0.5 g / m 2 The total dry weight of the resulting starch-based coating was about 1 g / m 2Furthermore, the cellulose-based substrate thus coated with the base layer was vapor deposition coated with an aluminum metallization coating 13, ie, an aluminum metallization layer, which was applied by physical vapor deposition onto the dried surface of the base coating 12 until a sheet resistance of 0.5 ohms / square was obtained.
[0213] The paper substrate thus metallized and coated with the base layer has another heat-stable gas barrier top coating 14 applied on the surface of the aluminum coating 13, the top coating consisting of PVOH (from Kuraray The thermally stable gas barrier top coating 14 has been applied and dried in the same manner as the base coating, and the dry weight of the top coating of the PVOH gas barrier composition is about 0.7 g / m 2 . The gas barrier PVOH composition top coating is sensitive to moisture, dirt and liquids, so at least another protective polymer layer or coating 15 is optionally applied over the PVOH top coating 14. The another layer or coating 15 can be a thermoplastic polymer, such as a polyolefin, such as LPDE or a vinyl adhesive polymer, such as EAA or a maleic anhydride graft copolymer with polyethylene. Typically such an additional polyolefin layer is required for measuring the oxygen permeability of a cellulose-based substrate coated with a barrier layer in order to cover any defects in the first PVOH coating, such as pinholes. If the additional protective coating 15 is made of a thermoplastic polymer or material, the laminate structure 10 itself will also be a heat-sealable barrier wrap or packaging material. The additional polymer layer or additional coating itself has no or very low inherent oxygen barrier properties and therefore will not further affect the measured oxygen permeability value. The additional protective polymer layer or coating 16 can be the same or different from the coating or layer 15 and can also be optionally applied to the other side of the cellulose-based substrate. Thus, a simple laminate 10 is obtained by simply adding the outermost protective polymer layers 15 and 16 to the barrier-coated cellulose-based substrate.
[0214] exist Figure 2 In the figure, a laminated packaging material 20 for packaging oxygen sensitive products (e.g. for liquid carton packaging) is shown, which includes a cellulose-based substrate 10 coated with a barrier layer; 25. The laminated material includes a flexural strength of 80 mN and about 200 g / m 2The packaging material is a paperboard main body layer 21 of paperboard having a grammage, and also includes an outermost protective (e.g., liquid-tight and heat-sealable) polymer layer 22 applied to the outer side of the main body layer 21, which side will face the outside of the packaging container made of the packaging laminate material. Layer 22 is transparent to show the printed decorative pattern 27 printed on the paper or paperboard main body layer to the outside. The printed pattern can thus inform the contents of the package, the packaging brand, and other information for consumers in retail facilities and food stores. The polymer of the outermost layer 22 can be a polyolefin, such as conventional low-density polyethylene (LDPE) of heat-sealable quality, but may also include other similar polymers, including LLDPE. Its application amount is about 12g / m 2 .
[0215] The innermost liquid-tight heat-sealable general layer 23 is arranged on the opposite side of the main body layer 21, which side will face the interior of the packaging container made of the packaging laminate material, that is, the layer 23 will be in direct contact with the packaged product. Therefore, the innermost heat-sealable layer 23 will form a strong transverse heat-seal portion of the liquid packaging container made of the laminated packaging material, which may include a combination of one or more polyethylenes, the polyethylene being selected from the group consisting of: LDPE, linear low-density polyethylene (LLDPE), and LLDPE prepared by polymerizing ethylene monomers with C4-C8 (e.g., C6-C8) α-olefin alkylene monomers in the presence of a metallocene catalyst (i.e., the so-called metallocene-LLDPE (m-LLDPE)). The application amount of the innermost liquid-tight heat-sealable general layer 23 may be 20 g / m 2 Up to 35g / m 2 .
[0216] According to a preferred embodiment, the innermost heat-sealable liquid-tight layer consists of a prefabricated oriented film 23a, which includes at least one partial layer of mainly linear low-density polyethylene (LLDPE). The film may also contain some LDPE. The thickness of the oriented film 23a is 12 μm to 25 μm, for example, a thickness of 15 μm to 20 μm, for example, a thickness of 18 μm.
[0217] The prefabricated oriented film 23a is laminated to the paper base 25 coated with the barrier layer, and laminated to the surface of the top coating of its PVOH 14 through an intermediate melt extrusion lamination adhesive layer portion 28 and / or another LDPE adhesive layer 23b, wherein the adhesive layer portion 28 includes an EAA tie layer with a thickness of 5μm to 8μm, and the other LDPE adhesive layer 23b is melt extrusion laminated with a thickness of 12μm to 20μm, for example, 12μm to 18μm.
[0218] The innermost heat-sealable layer 23 may alternatively consist of two or more coextruded partial layers (23a*, 23b*) formed from the same or different LDPE and m-LLDPE mixtures, which partial layers (23a*, 23b*) are formed by (a few g / m2 , for example 4 to 7 g / m 2 ) An intermediate coextruded, for example, ethylene acrylic acid copolymer (EAA) tie layer 28* adheres well to the surface of the heat-stable gas barrier top coating 14 of the barrier-coated paper substrate 25; 10, thereby bonding the innermost heat-sealable layer to the barrier-coated paper substrate 25; 10 and applying these layers together in a single melt coextrusion coating step.
[0219] The main body layer 21 is laminated to the Figure 1 The intermediate bonding layer 26 is formed by melt extrusion molding it as a thin polymer melt curtain between two paper webs, and thus laminating the main body layer and the paper substrate coated with the barrier layer to each other when all three layers pass through the cooled nip of the press rolls. The thickness of the intermediate bonding layer 26 is 12 to 18 μm, for example, 12-15 μm.
[0220] In an alternative embodiment, the bulk layer 21 can be laminated to the barrier-coated paper substrate 25 by wet lamination using an intermediate adhesive layer 26*, which is a thin layer of adhesive polymer, by applying an aqueous dispersion of a polyvinyl acetate adhesive to one of the surfaces to be adhered to each other and then pressing them together in a roller nip. Such a lamination step is performed at industrial speed in an efficient cold lamination or ambient lamination step without any energy-consuming drying operation to accelerate the evaporation of water. The dry coating weight of the intermediate adhesive layer 26* is only 3 to 4 g / m 2 , which means that drying and evaporation are not required.
[0221] Therefore, the above combined Figure 2 The amount of thermoplastic polymer in the laminate layer can be significantly reduced compared to the conventional melt extrusion laminated polyethylene adhesive layer 26 described.
[0222] exist Figure 3a , a process for aqueous dispersion coating 30a is shown, which can be used to apply an aqueous composition of gas barrier polymer coatings 12 and 14. A paper substrate web 31a (e.g. Figure 1The cellulose-based substrate 11 in the dispersion is conveyed to the dispersion coating station 32a, where the aqueous composition is applied to the top surface of the substrate by a roller. If the surfaces on both sides of the substrate are different, one side is usually more suitable for receiving a coating or printing a decorative pattern, so this is the surface to be coated in the present invention (this side is called the top surface or printing surface). Since the water content of the composition is 80-99% by weight, there will be a large amount of water on the wet-coated substrate, which needs to be heated, dried and evaporated to form a uniform continuous coating and have uniform quality in terms of barrier properties and surface properties (i.e., uniformity and low defect incidence). Drying is performed by a hot air dryer 33a, which also allows moisture to evaporate and be removed from the surface of the substrate. When the substrate surface passes through the dryer, the temperature of the substrate surface is always maintained below 95°C, for example, maintained between 60 and 95°C, for example, maintained between 70 and 90°C, for example, maintained between 80 and 90°C, for example, maintained below a temperature of about 85°C.
[0223] The resulting paper substrate web 34a coated with a gas barrier layer is sent for cooling and wound on a reel for intermediate storage. In an optional subsequent or later stage, the web coated in this way can be sent for further coating steps, for example to physically vapor deposit a gas barrier deposited coating 13 onto the paper substrate 11-12 coated with the base layer.
[0224] Figure 3b It is shown that the main layer 21 is first laminated to Figure 1 After the cellulose-based substrate 10 (i.e., 25) coated with the barrier layer is prepared, Figure 2 The process of the final lamination step of the packaging laminate material 20 is as follows.
[0225] As combined Figure 2 As described above, the main body paperboard 21 can be laminated to the paper substrate 10; 25 coated with the barrier layer by wet room temperature aqueous adhesive lamination or by melt extrusion lamination. Figure 3a The wet laminating adhesive is applied as described in the dispersion coating of , and lamination is performed by simply pressing the surfaces to be joined together without forcing the adhesive composition to dry. The main methods of melt extrusion lamination are described below Figure 3b shown.
[0226] The resulting paper pre-laminated web 31b is delivered from an intermediate storage reel, or directly from a laminating station for laminating the pre-laminated web of the bulk layer onto a cellulose based substrate coated with a barrier layer. The non-laminated side, i.e. the printed side, of the bulk layer 21 is melt extrusion coated at a cooled nip 33 by engagement with a molten polymer curtain 32 of LDPE which will form the outermost layer 22 of the laminate, extruded from an extruder feed block and die 32b. Subsequently, the pre-laminated bulk paper web, now with the outermost layer 22 coated on its printed side (i.e. the outer side), passes through a second extruder feed block and die 34b and a laminating nip 35, where a molten polymer curtain 34 is engaged and coated on the other side of the pre-laminated material, i.e. the barrier coated side of the paper substrate 10; 25. Thus, the innermost heat sealable layer 23a and the optional intermediate polymer layer 23b (optionally together with a tie layer of an adhesive polymer having functional groups to increase its bonding ability to adjacent layers) are co-extrusion coated onto the inside of the paper pre-laminated web to form the final laminated packaging material 20; 36, which is ultimately wound onto a storage reel (not shown).
[0227] The two coextrusion steps at the lamination roll nips 33 and 35 may alternatively be performed as two consecutive steps in reverse order.
[0228] According to another embodiment, one or both of the outermost layers can be applied in a separate pre-lamination station, where the coextrusion coating is first applied to the outside of the (printed) body paperboard layer and to the inside of the paper substrate coated with the barrier layer, and then finally the two pre-laminated paper webs can be laminated to each other as described above by extrusion lamination or wet lamination.
[0229] According to a preferred embodiment, the innermost layer of heat-sealable liquid-tight thermoplastic layers is applied in the form of a preformed polymer film 23a which is laminated to the coated side of the paper substrate 10; 25 coated with the barrier layer.
[0230] This pre-made film for the innermost layer 23a can be laminated to the barrier coated paper substrate 10; 25, which can be achieved by melt extrusion lamination (via melt extrusion of intermediate layers 23b* and / or 28) or alternatively, by wet ambient water-based adhesive lamination with an adhesive polymer intermediate layer 28*.
[0231] Figure 4Schematic diagram of an example of an apparatus for physical vapor deposition (PVD) of, for example, aluminum metal coating onto a web substrate of the present invention. A paper substrate 44 coated with a base layer is conveyed through a deposition chamber, in which a continuous evaporative deposition 40 of evaporated aluminum is carried out on its base layer coated side to form a metallized layer of aluminum. The thickness of the coating is 5 to 100 nm, for example 10 to 80 nm, preferably 10 to 50 nm, thereby forming a paper 43 coated with a barrier layer of the present invention. Aluminum vapor is formed by ion bombardment of an evaporation source of a solid aluminum sheet 41.
[0232] Figure 5a An embodiment of a packaging container 50a produced with a packaging laminate according to the invention is shown. The packaging container is particularly suitable for beverages, sauces, soups, etc. Typically, such a package has a volume of about 100 to 1000 ml. It can be of any structure, but is preferably brick-shaped, with longitudinal and transverse seals 51a and 52a, respectively, and optionally with an opening device 53. In another embodiment not shown, the packaging container can be formed into a wedge shape. In order to obtain such a "wedge shape", only the bottom part of the package is folded into shape so that the transverse heat seal at the bottom is hidden under the triangular flap, which is folded and sealed to the bottom of the package. The top transverse seal remains in the unfolded state. In this way, the packaging container, which is only partially folded, is still easy to handle and is stable enough in size to be placed on a shelf in a food store or on any flat surface,
[0233] Figure 5b An alternative example of a packaging container 50b produced with an alternative packaging laminate according to the present invention is shown. The alternative packaging laminate is thinner due to the thinner paper body layer, so it is not dimensionally stable enough to form a parallelepiped or wedge-shaped packaging container and is not folded into shape after the transverse seal 52b. The packaging container will remain a pillow-shaped bag-like container and be distributed and sold in this form.
[0234] Figure 5c A mountain-top package 50c is shown which is formed from a pre-cut sheet or blank, folded from a laminated packaging material comprising a paperboard bulk layer and a barrier-coated paper substrate of the present invention. Flat-top packages may also be made from similar blanks.
[0235] Figure 5d A bottle-shaped package 50d is shown which is a combination of a sleeve 54 formed from a pre-cut blank of the laminated packaging material of the present invention and a top 55 formed from injection-moulded plastic combined with an opening device such as a screw plug or the like. This type of package is marketed for example under the trade name Tetra and Tetra These particular packages are formed by attaching a molded top 55 with an attached opening device in a closed position to a tubular sleeve 54 of laminated packaging material, sterilizing the bottle-top capsule thus formed, filling it with the food product, and finally folding-forming the bottom of the package and sealing it.
[0236] Figure 6 The principle described in the introduction of the present application is shown, i.e. a web of packaging material is formed into a tube 61 by overlapping the longitudinal edges 62, 62' of the web and heat-sealing them to each other to thereby form an overlapping joint 63. The tube is continuously filled 64 with the liquid food to be filled and is divided into individual filled packages by repeated double transverse seals 65 of the tube, which are below the level of the contents filled in the tube and at a predetermined distance from each other. The packages 66 are separated by cutting between the double transverse seals (top seal and bottom seal) and are finally formed into the desired geometric configuration by folding along prepared crease lines in the material.
[0237] As a final remark, the invention is not limited to the embodiments shown and described above, but may vary within the scope of the claims.
Claims
1. A cellulose-based substrate (10) coated with a barrier layer, which is used as a barrier sheet in a heat-sealable laminated packaging material for packaging oxygen-sensitive products, the cellulose-based substrate (10) coated with a barrier layer comprising: a cellulose-based substrate (11), and a base coating (12) comprising more than 60% by weight of a material selected from the group consisting of starch, modified starch materials and cellulose ethers, the base coating (12) being applied to the surface of the first side of the cellulose-based substrate by dispersion or solution coating and subsequent drying to provide a smooth and thermomechanically resistant base coating, and A metallized coating (13) is further applied to the free surface of the base coating, the metallized coating being applied to the base coating by a vapor deposition method, wherein The barrier-coated cellulose-based substrate (10) further comprises a thermally stable gas barrier top coating (14) applied to the metallized coating (13) by dispersion or solution coating followed by drying, and wherein The thermally stable gas barrier top coating (14) is also coated with or laminated to a heat sealable thermoplastic material layer (15), the melting temperature of the thermally stable gas barrier top coating being higher than that of the heat sealable thermoplastic material layer, Thus, the barrier-layer-coated cellulose-based substrate has good gas barrier properties and enables robust induction heat-sealing conditions to be achieved in a laminated packaging material to manufacture packages from the laminated packaging material.
2. The barrier-coated cellulose-based substrate (10) according to claim 1, wherein the base coating (12) comprises more than 70 wt%, such as more than 80 wt%, such as more than 90 wt% of a material selected from the group consisting of starch, modified starch materials and cellulose ethers.
3. A cellulose-based substrate coated with a barrier layer according to any one of the preceding claims, wherein the base coating (12) has a dry weight of 0.5 g / m 2 Up to 2g / m 2 , preferably 0.5g / m 2 Up to 1.5g / m 2 amount applied.
4. A cellulose-based substrate coated with a barrier layer according to any one of the preceding claims, wherein the base coating (12) is applied as two consecutive coatings with intermediate drying, each consecutive coating having a dry weight of 0.2 g / m 2 Up to 0.8g / m 2 , for example 0.5g / m 2 Up to 0.7g / m 2 amount applied.
5. The barrier-coated cellulose-based substrate according to any one of the preceding claims, wherein the base coating (12) further comprises inorganic particles or fillers, for example in an amount of 1 to 30 wt%.
6. The barrier-coated cellulose-based substrate according to any one of the preceding claims, wherein the metallized coating (13) is a vapour deposited metal coating, such as an aluminium coating.
7. A barrier-coated cellulose-based substrate according to any one of the preceding claims, wherein the metallized coating (13) is applied by physical vapour deposition to a sheet resistance value of 0.25 to 0.75 Ω□, such as 0.4 to 0.6 Ω□.
8. A barrier-coated cellulose-based substrate according to any one of the preceding claims, wherein The thermally stable gas barrier top coating (14) comprises a polymer selected from the group consisting of vinyl alcohol polymers and copolymers, such as polyvinyl alcohol, PVOH, ethylene vinyl alcohol, EVOH, modified vinyl alcohol polymers and copolymers, and mixtures consisting essentially of such polymers, such as modified PVOH and modified EVOH.
9. The barrier coated cellulose based substrate according to any one of the preceding claims, wherein the thermally stable gas barrier top coating (14) further comprises a copolymer of ethylene and acrylic acid or methacrylic acid, EAA or EMAA.
10. The barrier-coated cellulose-based substrate according to any one of the preceding claims, wherein the thermally stable gas barrier top coating (14) has a dry weight of 0.5 g / m 2 Up to 2g / m 2 , preferably 0.5g / m 2 Up to 1.5g / m 2 amount applied.
11. A barrier-coated cellulose-based substrate according to any one of the preceding claims, wherein the thermally stable gas barrier top coating (14) is applied as two consecutive coats with intermediate drying, each consecutive coat having a dry weight of 0.2 g / m 2 Up to 1.5g / m 2 , for example 0.2g / m 2 Up to 1g / m 2 , for example 0.5g / m 2 Up to 0.8g / m 2 amount applied.
12. A barrier-coated cellulose-based substrate according to any one of the preceding claims, wherein the substrate is paper having a grammage of 30 g / m2 as measured according to ISO 536:2012. 2 Up to 70g / m 2 , density measured according to ISO 534:2011 is 800kg / m 3 Up to 1400kg / m 3 .
13. A method for producing a barrier-coated cellulose-based substrate (10) for use in a heat-sealable laminated packaging material for packaging oxygen-sensitive products, the method comprising the steps of: a) conveying a continuous web of cellulose-based substrate (11; 31a); b) providing an aqueous base coating composition comprising greater than 60 wt% on a dry weight basis of a material selected from the group consisting of starch, modified starch materials and cellulose ethers; c) applying the aqueous base coating composition to the top surface of the cellulose-based substrate web by dispersion coating (32a), such as roller coating; d) drying (33a) the applied aqueous gas barrier polymer coating from step c) to provide a smooth base coating (12); e) optionally repeating steps c) and d); f) vapor deposition coating (40) the base layer-coated and dried web substrate obtained from step e) with a metallized coating (13); g) applying (32a) an aqueous solution or dispersion of a thermally stable gas barrier top coating material to the metallized coating, for example by roller coating, h) drying (33a) the applied aqueous solution or dispersion from step g) to obtain a thermally stable gas barrier top coating (14), i) optionally repeating steps g) and h), j) thus obtaining a barrier-coated cellulose-based substrate having minimal defects in said base coating, said gas barrier top coating and said metallized coating, k) further coating the surface of the heat-stable gas barrier top coating with a heat-sealable thermoplastic material layer (15), the melting temperature of the heat-stable gas barrier top coating being higher than that of the heat-sealable thermoplastic material layer.
14. The method according to claim 13, wherein: The thermally stable gas barrier top coating (14) comprises a polymer selected from vinyl alcohol polymers and copolymers, such as the polymer selected from the group consisting of polyvinyl alcohol, PVOH, ethylene vinyl alcohol, EVOH, modified vinyl alcohol polymers and copolymers, and mixtures consisting essentially of such polymers, such as modified PVOH and modified EVOH.
15. A laminated packaging material (20) comprising a cellulose-based substrate (10; 25) coated with a barrier layer according to any one of claims 1 to 12, and further comprising a first outermost protective material layer (22) and a second innermost liquid-tight heat-sealable material layer (23; 23a; 23a*).
16. A laminated packaging material (20) comprising a cellulose-based substrate (10; 25) coated with a barrier layer according to any one of claims 1 to 12, and further comprising a first outermost liquid-tight heat-sealable polyolefin layer (22) and a second innermost liquid-tight heat-sealable polyolefin layer (23; 23a; 23a*).
17. The laminated packaging material (20) according to any one of claims 15 and 16, further comprising a main body layer (21) of paper or paperboard or other cellulose-based material and the cellulose-based substrate (10; 25) coated with the barrier layer being arranged inside the main body layer of paper or paperboard and between the main body layer and the second innermost liquid-tight heat-sealable material layer or polyolefin layer (23; 23a; 23a*).
18. The laminated packaging material (20) according to claim 17, wherein The barrier-coated cellulose-based substrate (10; 25) is bonded to the main body layer (21) via an intermediate bonding layer (26), the intermediate bonding layer (26) comprising a composition containing an adhesive selected from the group consisting of acrylic polymers and copolymers, starch, starch derivatives, cellulose and polysaccharide derivatives, polymers and copolymers of vinyl acetate and / or vinyl alcohol, and copolymers of styrene-acrylic latex or styrene-butadiene latex.
19. A laminated packaging material (20) according to any one of claims 15 to 18, wherein the second innermost layer of liquid-tight heat-sealable material (23) is a preformed polyolefin film (23a), such as an oriented polyethylene film comprising at least one layer of a majority of LLDPE polymer, to improve the robustness of the mechanical properties of the laminated packaging material.
20. A packaging container (50a; 50b; 50c; 50d) comprising a laminated packaging material as defined in any one of claims 15 to 19.
Citation Information
Patent Citations
Non-foil packaging laminate, method for manufacturing of the packaging laminate and packaging container thereof
WO2011003565A2
A method and a device for detecting defects in a packaging material
WO2012091661A1
Laminated packaging material, packaging containers manufactured therefrom
WO2017089508A1